Blood Pressure Changes during Pregnancy: Impact of Race, Body Mass Index, and Weight Gain - Magriples, Urania; Boynton, Marcella H.; Kershaw, Trace S.; Duffany, Kathleen O.; Rising, Sharon Schindler; Ickovics, Jeannette R. (American Journal of Perinatology, 2013)
Objective To investigate the effect of race, body mass index (BMI), and weight gain on blood pressure in pregnancy and postpartum.Study Design Secondary analysis of pregnant women aged 14 to 25 who received prenatal care at a university-affiliated public clinic in New Haven, Connecticut and delivered singleton term infants (n = 418). Longitudinal multivariate analysis was used to evaluate blood pressure trajectories from pregnancy through 12 weeks postpartum.Results Obese and overweight women had significantly higher blood pressure readings as compared with women with normal BMI (all p < 0.05). African American women who had high pregnancy weight gain had the greatest increase in mean arterial and diastolic blood pressures in pregnancy and postpartum.Conclusion Blood pressure trajectories in pregnancy and postpartum are significantly affected by race, BMI, and weight gain. Given the young age of this cohort, targeted efforts must be made for postpartum weight reduction to reduce cardiovascular risk.
Keywords: pregnancy; weight gain; obesity; racial differences